4th IEEE International Conference on Digital Ecosystems and Technologies 2010
DOI: 10.1109/dest.2010.5610593
|View full text |Cite
|
Sign up to set email alerts
|

Towards crowdsourcing translation tasks in library cataloguing, a pilot study

Abstract: Although automated translation systems are increasingly impressive they are still far from perfect, and even casual use demonstrates that they can"t produce robust, error free, transcriptions of arbitrary text. However it is becoming increasingly apparent that Crowdsourcing of translation tasks is not only viable but, in many cases, provides results equal to more expensive and slower alternatives. This paper provides a brief survey of academic and commercial systems that harness collective intelligence in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Initially, many people and organizations, especially in the cultural heritage domain, expressed doubts about utilizing crowdsourcing to achieve their goals. However, a study by Corney et al (2010) provided substantial evidence on employing crowdsourcing in a cultural heritage project, specifically in translation tasks, and showed that crowdsourcing had a 77% success rate. Other studies, of the Bentham project (Causer and Terras 2014) and the Papers of the War Department project (Leon 2014), also agree that involving crowdsourcing in a transcription project leads to a higher success rate than when text on paper is scanned and automatically transcribed using computer software.…”
Section: Crowdsourcing Approach In Digital Humanities and Heritagementioning
confidence: 99%
“…Initially, many people and organizations, especially in the cultural heritage domain, expressed doubts about utilizing crowdsourcing to achieve their goals. However, a study by Corney et al (2010) provided substantial evidence on employing crowdsourcing in a cultural heritage project, specifically in translation tasks, and showed that crowdsourcing had a 77% success rate. Other studies, of the Bentham project (Causer and Terras 2014) and the Papers of the War Department project (Leon 2014), also agree that involving crowdsourcing in a transcription project leads to a higher success rate than when text on paper is scanned and automatically transcribed using computer software.…”
Section: Crowdsourcing Approach In Digital Humanities and Heritagementioning
confidence: 99%
“…They proposed the following three step workflow to crowdsource the translation of non-Roman texts, i.e. language identification, translation of the text and remuneration (Corney, 2010).…”
Section: Internationalmentioning
confidence: 99%
“…Addressing the same concept Corney et al have proposed a workflow investigating the integration of crowd-sourcing translation into the cataloguing of foreign texts in libraries especially the non-roman ones [7].…”
Section: Background and Related Workmentioning
confidence: 99%